Sistem Pendukung Keputusan Penentuan Kelayakan Pemberian Kredit UMKM Menggunakan Metode AHP dan Weighted Product - Andhita Firman Syah Putra; A Sidiq Purnomo (Bulletin of Computer Science Research, 2025)
Microfinance institutions often conduct manual evaluations of creditworthiness for UMKM, resulting in subjective and inconsistent decisions. This study aims to develop a decision support system for determining creditworthiness for UMKM using the Analytical Hierarchy Process (AHP) and Weighted Product (WP) methods. AHP is used to evaluate the relative importance of criteria through pairwise comparisons. This process generates weights for each criterion with a consistency matrix as a validation tool. The results of the weighting are then used in the WP method, which calculates the final score for each prospective borrower by multiplying the performance value against the criteria and weights. The case study in this research is at the Koperasi Simpan Pinjam (KSP) Makmur Jaya. The results obtained show that the system is capable of producing objective alternative rankings, where prospective borrowers with the highest VI values are considered the most eligible to receive credit. After testing, the system also demonstrated consistency with manual calculations. Overall, this study shows that the combination of the Analytical Hierarchy Process (AHP) and Weighted Product (WP) can be effectively applied in multi-criteria decision-making in the microfinance sector.